Evaluation of type-2 diabetes progress in adult patients by using predictive algorithms - Nieto Chaupis, Huber (2016)
We used computational simulation inside a teleconsult scheme to predict the levels of diabetes progress of a sample of type-2 diabetes adult patients. Concretely, we have used computational algorithms to estimate the fraction of patients which would acquire diabetes complications such as necrosis, nephropathy and unexpected cardiovascular events. For this end, we have constructed a general function G which gives account of the behavior of glucose in time, but it is depending of up to 4 free parameters representing in somewhat: Diet, pharmacology, attitude of patient against the progress of disease, and a random number by the which it might be consistent with the binge eating disorder. From the results of this paper around 5±1 patients might increase their probabilities to pass to the subsequent diabetes such diabetic nephropathy.